(untitled) (Journal of Engineering, 2003)
The transient performance (acceleration and deceleration) analysis of turbojet gas turbine engire has been carried out in the present work. Transient simulation of the engines is based on the compatibility of flow and rotational speed but not of work. Gas turbine simulation is a general- purpose simulation developed for steady state (matching) study. Matching is achieved by zeroing the difference in mass flow rate of adjacent components, and work of compressor-turbine pairi Steady state is taken as an initial condition for transient simulation of the engine. The factors indicating engine limits such as surge margin, engine maximum temperature, and combustion chamber flameout that affect transient response has been studied. The results show that there is sudden change in the investigated parameters during transient operation, except for the rotational speed and the engine flow rate. Increasing the compressor surge margin and /or maximum turbine inlet temperature improves engine acceleration and decreases the acceleration time. Comparison with previous experimental work showed good agreement.